Assessing an empirical relationship between energy poverty and domestic health issues: A multidimensional approach. (15th April 2021) - Abbas, Khizar; Xie, Xiaoqing; Xu, Deyi; Butt, Khalid Manzoor
Abstract: Nowadays, it is imperative to examine potential health issues of household energy poverty, as in return, it leads to its reduction. Although extensive research has been done in other regions of the world, South Asia is overlooked in this regard. For this purpose, the study analyzes the health impacts of energy poverty in South Asia. First, it calculates the intensity and amount of energy poverty using a multidimensional index approach. Then, this study uses a one-way multivariate analysis of variance (MANOVA) to empirically examine the relationship between energy poverty and health problems analyzing a dataset from six South Asian countries. The results confirmed a statistically significant relationship of energy poverty with the sources of drinkable water, access to clean water, risks of mosquito bites, obesity, sterilization, marital status, literacy, occupation, and residence. After having robust findings, the study proposes effective policy measures to be taken to prevent energy poverty and control potential health consequences in South Asia. This study is an attempt to provide an empirical baseline to conduct further studies addressing a similar issue in other regions of the world. Graphical abstract: Image 1 Highlights: The study uses a dataset of 701, 834 households from six South Asian countries. It measures energy poverty with a multidimensional approach across South Asia. MANOVA is used to examine the causal relationship between health issues and MEPI. Most of the health variables have a statistically significant relationship with MEPI. The consistent results provide an evidence-based foundation for policy formulation.